PERTUMBUHAN DAN HASIL ENAM VARIETAS PADI SAWAH DATARAN RENDAH PADA PERBEDAAN JARAK TANAM - Tiur Hermawati (Bioplantae, 2012)
This research was aimed to evaluated the interaction effect of  plant spacing on the growth and yield of six lowland paddy  variety based on cuantitative characters.This research was conducted at  Jembatan Mas. Pemayung District. Jambi Province. This research was arrangement on Split plot  Design with Randomized block design (CRBD). The first factor as main plot : spacing J1 (30x20 cm), J2 (30x15 cm), J3 (30x10 cm), the second factor variety as subplot  :  V1 ( IR-42), V2 (Cisokan), V3 (IR-64), V4 (Batanghari), V5 (Wayrarem), V6 (Limboto). The Results showed that there were no interaction effect  between spacing and paddy variety. There are significantly simple effect of spacing to number of tillers and time of   flowering. Simple effect of Variety,have sfignificantly effect of variety to all growth and yield component. The highest paddy yield was achieved at Variety IR 42 ( 4.55 ton ha-1).   Key words : genetic variation, quantitative characters.